Determination of acoustical insulation coefficients: on site measurement and computational simulation - Ferreira, José Augusto Coelho (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper presents the in situ assessment of the acoustical insulation of 11 dwellings. The acoustical insulation indicators measured between rooms and for the façade, for all dwellings, were below the acoustical comfort values recommended by the German Standard DIN 4109. The acoustical insulation indicators were also obtained through computational simulation. Measured and simulated values were compared using the T-Hotteling statistical procedure (for small samples), indicating that the results from those two different sources were identical or very similar.